DEVELOPING A SUPPLEMENTARY BOOK ON RECOUNT TEXT MATERIAL FOR XI GRADE STUDENTS MAJORING IN MULTIMEDIA AT SMK DARUL HUDA - Widad Azhaar Annafi; Tyas Alhim Mubarok; Siti Rofi'ah (IKIP Siliwangi, 2023)
In 2022,The media in the English learning process is critical. This is evidenced by need analysis with 20 students and English teacher XI Grade in Multimedia students majoring. This paper aims to investigate the needs of students and also find out the result of development supplementary book on recount text materials. This study used Borg&Gall Research and Development model (R&D) to obtain results by using questionnaire and unstructured interview instrument. It is used some steps including (1)Research&Information collection,(2)Develop preliminary form of product,(3)Product revision, (4)Product testing,(5)Final product revision. The research subject is 20 students of XI Grade in Multimedia students majoring at Darul Huda vocational high school. The limitation of this study is developing a supplementary book on recount text material for XI Grade in Multimedia students majoring. This research finds that the supplementary book is valid in two aspects of content (84,8%) and media (76,4%) and feasible to use as supplementary book on recount text material. It is appropriate from satisfaction questionnaire about this product that percentage about 45% agree and 55% very agree. The last, this supplementary book is valid feasible to use as supplement about recount text material for XI Grade in Multimedia students majoring. Keywords: Recount Text; Supplementary Book; Vocational High School